The Usage of Economic Position in Understanding Indonesia’s Economy and the Pandemic Effects - Verico, Kiki (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
Before the global pandemic hit the economy in 2020, Indonesia had experienced two contractions in 1963 and 1998. These contractions come with hyperinflation, while the recent contraction of 2020 has not. This paper attempts to analyse the C-19 pandemic 2020 effects on the economy, which generates contraction but has a low inflation rate. On the opposite, the Asian Financial Crises (AFC) of 1998 caused negative economic growth andskyrocketing inflation. This paper applied descriptive data analysis and showed that the AFC affected the aggregate supply while the pandemic impacted the aggregate demand. This paper offers the usage of the proportion of inflation rate and economic growth rate and the annual sectoral growth rate comparison to describe Indonesia’s economic position and the pandemic effects.